Stochastic differential equations of charged particle motion in toroidal plasmas - Gurin, A.A.; Yavorskij, V.O. (Вопросы атомной науки и техники, 2017)
Stochastic equations of charged particle motion in toroidal plasma are derived using the Ito theory of stochastic processes. Expressions for stochastic differentials of the full set of drift variables associated with the kinetic theory of charged particles in plasma with Coulomb collisions are obtained. Equations obtained may be used for the modelling of fast charged particle motion in toroidal plasmas, namely for Monte-Carlo simulation the dynamics of charged fusion products and beam ions in tokamaks.